Réseaux d’affaires en justice. La concurrence et les pouvoirs (Couronne d’Aragon, xive siècle) - Claude Denjean (Criminocorpus)
The reticular analysis suits the legal documentation of the 14th century supplemented by notarial sources. It shows how institutions and multilateral control of reputation are articulated for protecting against risks the social categories that participate in financial dynamism. Studying emblematic cases proves how the constituent relations of social groups depend on their expected efficiency during the processual action. We can see how activate certain links within the network protect against characters who have become dangerous for profits. Fluid, versatile, modifiable, and diversely mobilized, mobilized networks prevail for business, without erasing the feudal structure, watermark, and rules of the game. They do not exclude or replace violence.